2017
DOI: 10.1186/s13104-017-2966-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hypertension among adults in Ethiopia: a community based cross-sectional study

Abstract: BackgroundHypertension is a growing public health problem in many developing countries including Ethiopia. It is a silent killer and most patients are detected to have it incidentally when they are admitted to hospital for unrelated disease or subjected to pre-employment or preoperative medical checkups. Information on the prevalence of hypertension and its associated factors is to be considered vital to focus and improve prevention and control of cardiovascular diseases. The study design was a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
75
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 34 publications
20
75
2
3
Order By: Relevance
“…This discrepancy could be because this study was conducted only in a community living in urban setting; whereas the study conducted in Gilgel Gibe Field Research Center south west Ethiopia was conducted in rural settings. Compared with other studies in Ethiopia, the finding of this study is much lower [10][11][12][13].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This discrepancy could be because this study was conducted only in a community living in urban setting; whereas the study conducted in Gilgel Gibe Field Research Center south west Ethiopia was conducted in rural settings. Compared with other studies in Ethiopia, the finding of this study is much lower [10][11][12][13].…”
Section: Discussioncontrasting
confidence: 89%
“…Having family history of hypertension, having high level of income, being male, being below grade 12, and having BMI ≥ 25 were significantly associated with hypertension for the overall study participants [12]. A study conducted in North West Ethiopia found the overall prevalence of hypertension to be 27.9%.…”
Section: Journal Of Community Medicine and Health Educationmentioning
confidence: 87%
“…The finding of the present study is consistent with the findings on the prevalence of hypertension in Hawassa (19.7%) (8) Mekelle (19.1%) (5) and the national prevalence (15.8%) (7). However, it is lower than the findings of the studies in Addis Ababa (32.3%) (15), Jigjiga (28.3%) (10), Durame (22.4%) (12), Bahir dar (23.5%) (22) and Gonder (28.3%) (13) and higher than the findings of the studies in Jimma (13.2%) (11) and Sidama zone (9.9%) (9). The discrepancy in the prevalence of hypertension might be attributable to the settings of the studies, the age group of the participants included in the studies and the life style of the population in the study areas.…”
Section: Discussioncontrasting
confidence: 58%
“…This study revealed that hypertension is associated with old age, excessive alcohol drinking, utilization of saturated fats/oils or unspecified different types of fats/oils and abnormal BMI. It has been mentioned by other reviewed studies that an increment in age has the effect on the blood pressure, which might be due to changes that happen in the walls of blood vessels as age increases (5, 10, 11). Similarly, consumption of excessive saturated fat/oil is also a risk factor for hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation